2014
DOI: 10.7860/jcdr/2014/7920.4507
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Examination Allied to Ultrasonography in the Assessment of New Onset Gynaecomastia: An Observational Study

Abstract: Aim: New onset gynaecomastia is a relatively common present ation to breast surgical services. The main aim of clinical and radiological evaluation is to exclude the presence of concurrent breast cancer. There exists much variability in the clinical assessment of male patients presenting with new onset gynaecomastia. Materials and Methods:In the presented pilot study, all the male patients presenting with new onset gynaecomastia to our department over a period of two years were studied.Results: Fifty three pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…From January 2011 to December 2015, 65 consecutive adult male patients (average 62.1 years, range 26-87) were recruited for the study. All patients were addressed by a first-line radiological centre for specialized advice and complementary examination at our regional Comprehensive cancer centre for unilateral (8) or bilateral (57, one of the two being suspicious) palpable masses. None of the patients had a personal history of breast cancer, chemotherapy or radiation therapy for any other cancer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From January 2011 to December 2015, 65 consecutive adult male patients (average 62.1 years, range 26-87) were recruited for the study. All patients were addressed by a first-line radiological centre for specialized advice and complementary examination at our regional Comprehensive cancer centre for unilateral (8) or bilateral (57, one of the two being suspicious) palpable masses. None of the patients had a personal history of breast cancer, chemotherapy or radiation therapy for any other cancer.…”
Section: Methodsmentioning
confidence: 99%
“…Other authors have found this diagnostic management controversial as cancer and gynaecomastia can coexist (21-55% of cases) 7 and as positive predictive value of a first-line mammography remains limited. 6,8 Consequently, the added value of each imaging modality and their place in diagnosis management remains unclear.…”
mentioning
confidence: 99%
“…The majority of male breast lesions are benign; malignancy of the male breast is rare [ 1 ], accounting for only 0.7% to 1% of all breast cancers and 0.17% of all cancers in men [ 2 , 3 ]. Gynecomastia within the subareolar regions is the most common benign condition of the male breast in newborns, adolescents, and the elderly [ 2 , 3 ]. Gynecomastia is seen histologically in 50% of all men at autopsy [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A non-calcified mass is the most common mammographic finding in male breast cancer [ 2 ]. However, some case reports have shown that male breast cancers were not detected by mammography [ 3 ]. There are no statistically significant differences between the sensitivity and specificity of mammography and US in diagnosing male breast lesions [ 2 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation